Coats-Like reaction post-vitreoretinal surgery for PDR managed with laser photocoagulation and adjunctive intravitreal steroids– a case report - Kanika Godani; Shruti Vidyasagar; Preksha Biradar; Vishma Prabhu; Prathiba Hande; Priyanka Gandhi; Rupal Kathare; Jay Chhablani; Ramesh Venkatesh (BMC Ophthalmology)
Abstract Purpose To report a rare case of a Coats-like response developing after vitreoretinal surgery for proliferative diabetic retinopathy (PDR) and its successful management with retinal laser photocoagulation and adjunctive intravitreal steroids. Case description A 52-year-old woman with a five-year history of type 2 diabetes mellitus and hypertension presented with decreased vision in the left eye (counting fingers at 1 m). Examination revealed high-risk PDR in both eyes, with a subtotal macula-off combined retinal detachment in the left eye. The patient underwent pan retinal photocoagulation for the right eye and vitreoretinal surgery with silicone oil tamponade for the left eye. Postoperatively, the retina remained attached, but progressive increase in hard exudates in the inferotemporal quadrant was noted in the left eye. Wide-field fluorescein angiography showed temporal capillary dropout and leakage corresponding to the exudates, consistent with a Coats-like response. Results Silicone oil removal combined with targeted endolaser photocoagulation and intravitreal triamcinolone acetonide injection resulted in a complete resolution of the subretinal lipid exudation. Two weeks postoperatively, the retina remained well-attached, but best-corrected visual acuity declined to 6/60 due to posterior subcapsular cataract progression. Optical coherence tomography confirmed the resolution of subretinal lipid exudation, and the patient was advised to undergo cataract surgery. Conclusion This case highlights the occurrence of a Coats-like response following vitreoretinal surgery for PDR, potentially triggered by retinal ischemia and surgical inflammation. Timely intervention with laser photocoagulation, and adjunctive intravitreal corticosteroids can effectively manage such responses.